Ultrasonography imaging study of thoracic organ in goat - Sulaiman, Nurul Syahirah Husna (2016)
Ultrasonography is a non-invasive tool that is less commonly used for thoracic examination in goat. In this study, the thoracic organ which is the heart and lung is examined by using the ultrasonography technique to describe the structure and the anatomical location of the organ. Five animals were clipped from area caudal to scapula until the last rib for both left and right thorax. Coupling gel was applied to the transducer. Examination was done for both left and right side of the thorax by using the 5 MHz convex and linear probe. In echocardiography, five imaging plane were obtained from the right and two from the left side of the 4th intercostal space. Lung ultrasound shows the hyperechoic horizontal line with reverberation artifact. In conclusion, all echocardiography imaging plane were obtain at the 4th intercostal space slightly 2 cm above the olecranon and lung ultrasound is at between the 7th until 11th intercostal space.